ТАРИХ ТАЪЛИМИДА МЕДИАКОНТЕНТЛАРДАН САМАРАЛИ ФОЙДАЛАНИШНИНГ МУҲИМ ШАРТЛАРИ - Толепов, Б. (SCIENCE and SOCIETY, 2025)
The article discusses the important conditions for the effective use of media content in teaching history and the role of the teacher in this process.
Keywords: teaching history; content; conditions for using media content